Prognostic and Clinicopathological Significance of MUC Family Members in Colorectal Cancer: A Systematic Review and Meta-Analysis - Chao Li; Didi Zuo; Tao Liu; Libin Yin; Chenyao Li; Lei Wang (Gastroenterology Research and Practice)
Objective. To assess the association between MUC expression levels in colorectal cancer (CRC) tissues and prognosis and investigate the associations between MUC expression levels and CRC clinicopathological characteristics. Methods. The PubMed, Embase, Cochrane Library, and Web of Science databases were searched from inception through September 13, 2019, to identify studies investigating the association between MUC expression levels in CRC tissues and prognosis. Pooled hazard ratios (HRs) or odds ratio (ORs) with 95% confidence intervals (CIs) were used to evaluate associations between MUC expression levels and prognosis or clinicopathological characteristics, respectively. The heterogeneity between studies was assessed by the I2 values, whereas the likelihood of publication bias was assessed by Egger’s linear regression and Begg’s rank correlation test. Results. Among 33 included studies (n=6032 patients), there were no associations between combined MUC phenotype expression levels and overall survival (OS) or disease-free survival (DFS)/relapse-free survival (RFS) in patients with CRC. In subgroup analyses, the upregulated MUC1 expression (HR=1.50; 95% CI, 1.29–1.74; P<0.00001) was associated with poor OS. However, the upregulated MUC2 expression (HR=0.64; 95% CI, 0.52–0.79; P<0.00001) was associated with better OS. Furthermore, a high level of MUC1 expression (HR=1.99; 95% CI, 0.99–3.99; P=0.05) was associated with shorter DFS/RFS. However, patients with a low level of MUC2 tumors showed better DFS/RFS than patients with a high level of MUC2 tumors (HR=0.71; 95% CI, 0.49–1.04; P=0.08; P=0.0.009, I2=67%) and MUC5AC expression (HR=0.56; 95% CI, 0.38–0.82; P=0.003) was associated with longer DFS/RFS. In addition, a high level of MUC1 expression was associated with CRC in the rectum, deeper invasion, lymph node metastasis, distant metastasis, advanced tumor stage, and lymphatic invasion. A high level of MUC2 expression had a protective effect. High secretion of MUC5AC is associated with colon cancer compared with rectal cancer. Conclusion. The protein expression of MUC1 might be a poor biomarker in colorectal cancer and might play a role in tumor transformation and metastasis. However, the protein expression of MUC2 expression might have a protective effect. Furthermore, randomized controlled trials (RCTs) of large patients are needed to confirm the results.